How does the ECB allot liquidity in its weekly main refinancing operations? A look at the empirical evidence - Livio Stracca; Steen Ejerskov; Clara Martin Moss (European Central Bank (ECB), 2003)
This model provides a simple weekly model of the regular supply of liquidity in the euro area, with a view to understanding the functioning of the euro area money market. The main result of the analysis is that liquidity has normally been provided by the ECB in a neutral and smooth manner, but also that there has been attempt, albeit very limited, to correct deviations of the overnight rate from the main refinancing rate. Moreover, the paper finds that liquidity has affected the overnight interest rate to a significant extent only after the last main refinancing operation of the maintenance period, when it is not possible for the ECB to adjust liquidity imbalances except by making recourse to fine-tuning operations.
Keywords: E52; E43; G21; 330; Bank reserves; liquidity effect; liquidity policy; martingale hypothesis; monetary policy